Waitress Development in Improving Performance in Hotel and Restaurant Businesses in Parepare City - I Putu Suarta (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the development of waiters and waitresses in improving performance in hotel and restaurant businesses in Parepare City. The background of the study is based on the strategic role of waiters as the spearhead of service that is directly related to customer satisfaction and loyalty. The research method uses a qualitative approach with data collection techniques through interviews, observations, and documentation studies of hotel and restaurant managers. The results show that most waiters and waitresses in Parepare have not received adequate professional training, either in technical skills or soft skills, so that service quality is not optimal. The main constraints are limited training facilities, low work motivation, and the lack of sustainable human resource development programs. This study recommends the need for competency-based training, improved training facilities, foreign language proficiency, and local government support in implementing waiter development programs. Thus, it is hoped that the quality of hotel and restaurant services in Parepare City can improve, support business competitiveness, and strengthen the city's image as a tourism destination.